Company Performance Appraisal Analysis Using Balanced Scorecard At Madjatea Shopperba - Haris Fauzi; Nita Hernita (Nomico, 2024)
The problem that occurred at MadjateaMajalengka Department Store was a decrease in sales which resulted in a decrease in store turnover and income. This decrease is an evaluation of the use of the Balance Scorecard performance measurement method that is being tried to be applied.This study aims to determine the performance analysis of MadjateaDepartment Stores using the Balance Scorecard method. The variables used are a financial perspective, customer perspective, internal business perspective and learning and growth perspective. This study uses primary data from questionnaires and secondary data from MadjateaToserba's financial reports. The method used in this study is a survey method with a descriptive and verification approach. The sampling technique used is saturated sampling technique with a total of MadjateaDepartment Store employee respondents. The analytical tool used in this study is the Balanced Scorecard method with 4 approaches.The results of this study indicate that the performance of Madjatea Department Stores using the Balanced Scorecard method found that the financial perspective is categorized as healthy, the customer perspective is categorized as unhealthy, the internal business perspective is categorized as unhealthy and the learning and growth perspective is categorized as unhealthy. So it is necessary to increase the 3 unhealthy aspects by using the Madjatea Department Store performance measurement through the balanced scorecard method.